How Nurse Experience Influences the Patterns of Electronic Medical Record Documentation in an Intensive Care Unit. (November 2019) - Guo, Wenbin; Kim, Jung Hyup; Smith, Benjamin; Despins, Laurel
The primary objective of this study is to explore how nurse experience influences the patterns of documenting in electronic medical records (EMR) in an intensive care unit (ICU). To understand the time and work patterns related to EMR documentation, the real-time measurement system data was used. This log data is a representation of actions taken by ICU nurses during EMR documentation. To analyze the ICU nurse's workflow related to EMR documentation, a hierarchical task analysis (HTA) was conducted. Multiple HTA charts were used to identify different patterns of EMR documentation between more experienced nurses and less experienced nurses. The results revealed that the nurse's experience had significant impacts on the frequency of updating the assessment result page and reviewing clinical results in EMR. The findings from this study will contribute to revealing unknown usability problems of EMR documentation process.